Sistem Informasi Penjualan Pada Toko Rial-Harmonika Berbasis Website - Fahlevi, Reza (Journal Information Technology Trends (JITRENDS), 2024)
Rial-Harmonika is a business entity focused on the sale, production, and installation of harmonica screens. However, this company faces challenges in managing orders and customer service, such as manual transaction recording systems that increase the risk of data loss. To address these issues, the author proposes implementing information technology titled "Sales Information System at Rial-Harmonika Store Based on Website". This system uses the Laravel 10 framework, which has advantages such as Blade Templating Engine, Migrations and Seedings, Artisan Command Line Tool, and easy-to-understand documentation. This system enables administrators to manage product data and process purchase data, as well as offering ease of access for customers to view products and place orders.